2014
DOI: 10.1128/jvi.03562-13
|View full text |Cite
|
Sign up to set email alerts
|

A Broadly Neutralizing Human Monoclonal Antibody Directed against a Novel Conserved Epitope on the Influenza Virus H3 Hemagglutinin Globular Head

Abstract: Most neutralizing antibodies elicited during influenza virus infection or vaccination target immunodominant, variable epitopeson the globular head region of hemagglutinin (HA), which leads to narrow strain protection. In this report, we describe the properties of a unique anti-HA monoclonal antibody (MAb), D1-8, that was derived from human B cells and exhibits potent, broad neutralizing activity across antigenically diverse influenza H3 subtype viruses. Based on selection of escape variants, we show that D1-8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
48
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 40 publications
1
48
0
2
Order By: Relevance
“…Cross-reactive HA-specific antibodies might target the conserved region near the receptor-binding site of hemagglutinin head, although the majority of HA cross-reactive antibodies would recognize the stem region26272829. Other conserved neutralizing epitopes on the H3 HA head have also been described3031. Nevertheless, it is unclear about the protective level of these cross-reactive HA-specific antibodies and the declining trend of the HI titer with the time within previously vaccinated individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-reactive HA-specific antibodies might target the conserved region near the receptor-binding site of hemagglutinin head, although the majority of HA cross-reactive antibodies would recognize the stem region26272829. Other conserved neutralizing epitopes on the H3 HA head have also been described3031. Nevertheless, it is unclear about the protective level of these cross-reactive HA-specific antibodies and the declining trend of the HI titer with the time within previously vaccinated individuals.…”
Section: Discussionmentioning
confidence: 99%
“…An H5N1-specific mouse MAb HA-7 was shown to recognize a structural epitope that consists of two segments, NV/PE at residues 87-79 and HFEKIW at residues 113-118; the latter overlaps the epitope identified in this study [27]. A HuMAb D1-8, which is derived from human antibody VH and VL repertoires and specific to H3 influenza viruses, was reported to target a conserved epitope between antigenic sites D and E at the globular head of H3 HA [25], which correspond to Ca1 and Cb, respectively, in H1 HA.…”
Section: Discussionmentioning
confidence: 77%
“…Most heterosubtypic crossneutralizing HuMAb have been reported to recognize epitopes located mainly in the most conserved HA stem region [7,10,14,23]. Also, a few HuMAbs that target relatively conserved epitopes adjacent to or overlapping the RBS in the head region were shown to be subtype-specific [17,25,26]. To our knowledge, 5D7 is the first heterosubtypic neutralizing HuMAb that targets a conserved epitope distinct from the RBS in the HA globular head region.…”
Section: Discussionmentioning
confidence: 91%
“…76 Benjamin et al 77 described the discovery of a unique anti-HA mAb, D1-8, that was derived from human B-cells and exhibits potent, broad neutralizing activity across antigenically diverse influenza H3 subtype viruses. D1-8 targets a novel epitope on the globular head region of the influenza virus HA protein.…”
mentioning
confidence: 99%
“…D1-8 targets a novel epitope on the globular head region of the influenza virus HA protein. 77 More recently, Skountzou et al 78 have demonstrated in mice that IgM antibodies are functionally similar to IgG, as they neutralized the influenza virus in the presence of complement.…”
mentioning
confidence: 99%